Levon Ter-Petrossian, Armenia Future, Relations with Turkey, and the Karabagh Conflict, edited by Arman Grigoryan, Palgrave Macmillan, Cham 2018, ss. 174. - Czachor, Rafał (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2020)
Recenzja